Penerapan Strategi Pembelajaran Poster Session Dalam Meningkatkan Kemampuan Metakognisi Siswa Pada Mata Pelajaran Fiqih Siswa Kelas VIII Di Madraah Tsanawiyah Negeri 1 Langkat - Fika Agustari, Usmaidar, Ahmad Fuadi (CV. PUSDIKRA MITRA JAYA, 2022)
This study aims to determine the critical thinking skills of students in Fiqh learning after the application of the Poster Session Learning Strategy in class VIII MTs N 1 Langkat. This research is included in class action research (Action Research). This research uses a type of collaborative model, namely researchers with Fiqh study teachers in class VIII MTs N 1 Langkat. the instruments in this researcher are observation sheets and tests in accordance with research procedures by observing cycle I and cycle II. The subjects of this study were students of class VIII 6 MTs N 1 Langkat in the 2022/2023 school year totaling 32 people, teachers teaching fiqh subjects, and all components that were part of this study. Based on the data exposure above, it can be concluded that the metacognition ability of students in fiqh subjects before using the poster session strategy is still relatively low, this is known from the completeness of learning in class VIII MTs N 1 Langkat in the pre-cycle is 43.75% while in cycle I it reaches 71.87% and in cycle II it is 86.25%. The application of the Poster Session strategy in fiqh subjects at MTsN 1 Langkat is in accordance with the steps of the learning strategy. This Poster Session strategy is one of the active learning methods because in the application of this method students are required to play an active role, namely free to express their opinions about the material to their friends, this of course trains their thinking skills. In its implementation, the application of the Poster Session Strategy can be carried out well through two cycles. This can be seen through the activities of students in cycle I and cycle II have increased. The results of observations of student activity in learning which initially in cycle I only reached a score of 70% then increased by 20% to 90% in cycle II. After the application of the Poster Session Strategy, students' metacognition abilities have increased, this can be seen from the results of the pre-cycle metacognition ability test which only reached an average score of 68, 43 (less) and increased in cycle I to 73.52 (sufficient) and in cycle II increased again to 86.25 (good). The increase in metacognition skills can also be seen in the increase in the percentage of student completeness, namely in the pre-cycle only 43.75% while in cycle I it reached 71.87% and in cycle II it was 87.5%.